1965
DOI: 10.5038/1827-806x.1.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Algological investigations in Mammoth Cave, Kentucky

Abstract: Algological Investigations in Mammoth Cave, KentuckyWith plate 104 (1) and one figure in the text IntroductionBiospeleology in the United States is still in its early descriptive period and though the situation has greatly improved since 1931 when Bolivar and Jeannel could make the following statement:" ... les naturalistes americaines n'ont enterpris aucune etude serieuse de la faune de l'immense domaine souterraine qui s'offre a leurs investigations. On chercherait en vain dans les collections des Musees un … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1965
1965
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
1
8
1
Order By: Relevance
“…There were two species (Chlorella miniata and Achnanthes minutissima) identified in our and from Van Hoff's (1974) study. There was one species (Chroococcus minor) similarity between Van Hoff and our study; only one other species (Jaaginema neglectum) was identified by two studies (Jones, 1965;Nagy, 1965). A difference in the taxonomists identifying the lamp flora may account for some of species disparity between these studies.…”
Section: Resultscontrasting
confidence: 38%
See 2 more Smart Citations
“…There were two species (Chlorella miniata and Achnanthes minutissima) identified in our and from Van Hoff's (1974) study. There was one species (Chroococcus minor) similarity between Van Hoff and our study; only one other species (Jaaginema neglectum) was identified by two studies (Jones, 1965;Nagy, 1965). A difference in the taxonomists identifying the lamp flora may account for some of species disparity between these studies.…”
Section: Resultscontrasting
confidence: 38%
“…Jones and Table 4. Cyanobacteria lamp flora identified from Jones (1965), Nagy (1965), Van Hoff (1974) and Harris (1981). Table 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-All of the algae identified from Mammoth Cave (except for a few doubtful references to "Protococcus") were found in, or cultured from samples made by George Claus and T. Barr on August 28, 1963. The taxonomy of these algae has been discussed in detail by Jones (1965) and Van Landingham (1965. The location of these stations, Claus' original notations, some supplementary remarks, and the species of algae found by Jones and Van Landingham are given below.…”
Section: The Floramentioning
confidence: 99%
“…Fig. 1 This species seems to be a cosmopolitan, widespread form and has also been found in Mammoth cave' (Jones, 1964). Observed both without and with culturing.…”
Section: Cllajl1aesi Phon Gracilismentioning
confidence: 99%